(untitled) (Research, Society and Development, 2023)
Because of hydrological changes in the lower São Francisco River, the objective of this research was to identify socio-cultural aspects among artisanal fishers and their understanding of fish species dynamics in the fluvial plain. The study was conducted in the micro-region of Penedo by using semi-structured interviews. We also collected fish during low tide using cast nets or gill nets to survey the ichthyofauna of the river plain, identifying the dominant fish species and their diversity. There is a substantial dependence of fishermen’s families on fishing activities, which are associated with the region’s low education level and limited employment opportunities. The remuneration for the activity is low, which negatively affects the food security of these individuals. There is a perception of changes in the dynamics and decline in the occurrence of fish species, resulting from decreased flows and destructive fishing methods. A total of 3,055 individuals comprising 82 taxa and 30 families were collected. The fish fauna on the fluvial plain is composed mainly of species associated with estuaries, especially near the municipalities of Piaçabuçu and Penedo. The environmental mitigations of the hydropower plants and the revitalization program were insufficient to solve the problems in the region.